Penentuan Harga Obligasi Callable dengan Suku Bunga Black Derman Toy Menggunakan Pohon Binomial - , HELIDA HAERINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Interest rate has an important role in the pricing of financial assets, one of them is a bond. Callable bond is a bond that gives the issuer the right to buy back the bonds at a certain price over the life of the bonds. In estimating bond pricing used binomial tree. For a constant interest rate, it is not difficult to determine the bond price. But in fact, interest rates move up and down uncertainy and it is a stochastic process. So to observe the stochastic process, needed interest rate stochastic model. In this thesis, used single factor interest rate model that developed in 1990 by Fischer Black, Emanuel Derman, and William Toy and assumed that short rate has a lognormal distribution and has no-arbitrage assumption. That model is Black Derman Toy (BDT) short rate model. BDT short rate model used in the bisection method to find the value of drift. BDT short rate model also incorporate mean reversion in it. In determining the binomial tree, the interest rate is modeled forward first, and then backwards in determining bond prices.